Bangladesh : Climate Change and Sustainable Development - World Bank (Washington, DC, 2013)
The study examines Bangladesh's extreme vulnerability to climate change, whose low-lying topography, and funnel-shaped coast, further exposes the land to cyclones, and tidal surges, resulting in seasonal floods. These factors, and the large population base, widespread poverty, aggravated by the lack of strong institutional development, makes the country particularly vulnerable to climate variability. Various climatic factors, i.e., temperature, precipitation, evaporation, etc., are identified, and possible climate change scenarios are discussed for possible adaptation. The potential effects of climate change are summarized, confined up to the year 2050, stipulating that climate change will also affect cross-boundary river flows, and that the reported events of the El Nino Southern Oscillation, have influenced the record-breaking floods of 1987, 1988, and 1998. The study identifies critical impacts that development policymakers will have to consider in a warmer Bangladesh: drainage congestion problems; reduced fresh water availability; disturbance of morphological processes; and, an increased intensity of disasters. Reasons to adopt an anticipatory, long-term strategy in adapting to climate change are discussed, and an assessment criteria is proposed. Recommendations include active participation in international debates on climate change, incorporating climate change considerations in water sharing negotiations, and, viewing climate change not just as an environmental concern, but as a major development issue.